You need to remember that the primitive integral is a differentiable function whose derivative is `f(x)` , such that:

`F'(x) = f(x)`

Hence, you need to differentiate the function `F(x)` with respect to `x` , using the quotient rule, such that:

`F'(x) = ((x^2-1)'(sqrt x) - (x^2-1)(sqrt x)')/((sqrt x)^2)`

`F'(x) = (2xsqrt x - (x^2-1)/(2sqrtx))/x`

`F'(x) = (4x*sqrt x*sqrt x - x^2 + 1)/(2xsqrt x)`

`F'(x) = (4x^2 - x^2 + 1)/(2xsqrt x)`

`F'(x) = (3x^2 + 1)/(2xsqrt x)`

Rationalizing yields:

`F'(x) = (sqrt x*(3x^2 + 1))/(2x^2) = f(x)`

**Hence, evaluating the function `f(x)` , under the given conditions, yields **`f(x) = (sqrt x*(3x^2 + 1))/(2x^2).`

**Further Reading**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now